Personal recovery of young adults with severe anorexia nervosa during adolescence: a case series - Piot, Marie-Aude; Gueguen, Juliette; Michelet, Daphné; Orri, Massimiliano; Köenig, Marie; Corcos, Maurice; Cadwallader, Jean-Sébastien; Godart, Nathalie (Eating and weight disorders, 2020)
Purpose Despite the emergence of a growing qualitative literature about the personal recovery process in mental disorders, this topic remains little understood in anorexia nervosa (AN), especially severe AN during adolescence. This cases series is a first step that aims to understand recovery after severe AN among adolescents in France, from a first-person perspective. Methods This cases series applied the interpretative phenomenological analysis (IPA) method to data collected in semi-structured face-to-face interviews about the recovery process of five young women who had been hospitalized with severe AN 10 years earlier during adolescence. Results A model of recovery in four stages (corseted, vulnerable, plastic, and playful) crossing seven dimensions (struggle and path of initiation; work on oneself; self-determination and help; body; family; connectedness; and timeline) emerged from the analysis. New features of the AN personal recovery process were characterized: bodily well-being and pleasure of body; stigmatization; the role of the group; relation to time; and importance of narratives. We suggest a new shape to model the AN recovery process, one that suggests several tipping points. Recruitment must now be widened to different AN contexts. Conclusions The personal recovery paradigm may provide a new approach to care, complementary to medical paradigm. Registration of clinical trial No. NCT03712384. Our study was purely observational, without assignment of medical intervention. As a consequence, this clinical trial was registered retrospectively. Level of evidence Level V, descriptive study.